Efficacy and safety of TACE combined with traditional Chinese medicine versus TACE alone in hepatocellular carcinoma: bayesian network meta-analysis and pharmacological mechanisms study - Chen, Li; Zhu, Xiu-Ling; Lin, Jie; Li, Dong-Liang (Frontiers in Pharmacology, 2024)
Chinese Medicine (TCM) with Transarterial Chemoembolization (TACE) in hepatocellular carcinoma (HCC) treatment via meta-analysis and an exploration of network pharmacology analysis (NPA).A comprehensive search across different databases retrieved all randomized controlled trials (RCTs) evaluating TCM combined with TACE for HCC.Meta-analysis included 39 RCTs to assess the intervention effects. The bayesian network meta-analysis observed the relative efficacy and potential ranking of various interventions. Active compounds and target genes from frequently used TCM were sourced from the TCMSP database, while HCC disease targets were collected from five public disease databases. Regulatory networks connecting target genes with active components of key herbs were constructed. Following the identification of key genes, we conducted analyses of Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) to enrich our understanding of their functions. NPA and molecular docking methods were refined to reveal potential interactions between TCM components and their specific targets.The combination of TCM with TACE significantly enhances the efficacy and safety of HCC treatment, improving the overall response rate, disease control rate, and overall survival rate, while also reducing the incidence of adverse events. Among the TCM evaluated, Ganfu Formula proved to be the most effective in enhancing patient response rates. Analysis of all included medicinal herbs identified 10 pivotal TCMs and 17 core genes. GO analysis revealed their significance in protein interactions, whereas KEGG analysis highlighted their role in crucial oncological pathways. NPA and molecular docking techniques elucidate the underlying mechanisms of action of TCM components.Adding TCM to TACE protocols significantly enhances treatment outcomes and safety in HCC patients by modulating tumor biology and systemic immune responses, highlighting its potential as an effective adjunct therapy. These findings support the inclusion of TCM in standard care regimens, offering potential for improved management of HCC.